Automotive Window Glass
The laminated automotive window glass with an antifouling layer addresses the issue of dirt adhesion by providing effective prevention and easy cleaning, enhancing visibility and durability.
Patent Information
- Application Number
- JP2021058896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-03-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Automotive window glasses lack antifouling performance to prevent dirt adhesion and require improved methods to maintain cleanliness.
A laminated automotive window glass with a first functional layer having antifouling properties, applied to specific areas of the glass surface, and a shielding layer to prevent adhesion and facilitate easy cleaning.
The antifouling layer effectively prevents dirt adhesion and allows easy removal, reducing static electricity and preventing scratches, while maintaining visibility and aesthetic appeal.
Smart Images

Figure 0007607494000012 
Figure 0007607494000013 
Figure 0007607494000014
Abstract
Description
[Technical field]
[0001] The present invention relates to automotive glazings. [Background technology]
[0002] Automobile window glass is laminated with various functional films that exhibit water repellency, light blocking properties, etc. Such functional films are laminated by various methods (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-20204 A Summary of the Invention [Problem to be solved by the invention]
[0004] Meanwhile, the requirements for the functions of automobile window glass have become more diverse, and in recent years, there has been a demand for anti-soiling performance that makes it difficult for dirt to adhere to the glass. An object of the present invention is to provide an automobile window glass having anti-soiling performance. [Means for solving the problem]
[0005] Item 1. Automotive window glass, A plate-shaped glass body; A first functional layer that is laminated on the vehicle interior surface of the glass body and has at least an antifouling property; The automotive window glass comprises:
[0006] Item 2. The automobile window glass according to item 1, wherein a predetermined marking is stamped on the surface of the glass body facing the interior of the vehicle.
[0007] Item 3. The automobile window glass according to item 1, wherein a predetermined marking is stamped on the surface of the glass body facing the vehicle exterior.
[0008] Item 4. The automobile window glass according to any one of Items 1 to 3, wherein the glass body is curved so that the interior side of the vehicle is concave.
[0009] Item 5. The automobile window glass according to any one of Items 1 to 3, wherein the glass body is formed into a flat plate shape.
[0010] Item 6. Further includes a shielding layer laminated on a part of the surface of the glass body on the vehicle interior side, Item 6. The automotive window glass according to any one of items 1 to 5, wherein the first functional layer is laminated on at least a part of the region where the shielding layer is not laminated on the vehicle interior surface of the glass body and at least a part of the shielding layer.
[0011] Item 7. The automobile window glass according to item 6, wherein the shielding layer has a first region in which the first functional layer is not laminated.
[0012] Item 8. The automobile window glass according to item 7, wherein the first region is a portion that comes into contact with a vehicle body.
[0013] Item 9. The automotive window glass according to item 7, wherein the first region is a region for mounting a component.
[0014] Item 10. The glass body is a windshield, Item 10. The automotive window glass according to any one of items 6 to 9, wherein a second region in which the first functional layer is not laminated is provided in a region in which the shielding layer is not laminated on the vehicle interior surface of the glass body.
[0015] Item 11. The glass body is a side glass, A third region in which the first functional layer is not laminated is provided along the lower edge of the glass body, 5. The automotive window glass according to any one of items 1 to 4, wherein a part supporting the side glass is attached to the third region.
[0016] Item 12. The glass body is a side glass, 5. The automotive window glass according to any one of items 1 to 4, wherein a fourth region in which the first functional layer is not laminated is provided on the vehicle interior surface of the glass body.
[0017] Item 13. The automobile window glass according to item 11 or 12, wherein the boundary between the first functional layer and the third region is formed in a wavy shape.
[0018] Item 14. An automobile window glass according to any one of Items 1 to 13, wherein the average molecular weight of the composition exhibiting the antifouling property in the first functional layer is 1,000 or more and 30,000 or less.
[0019] Item 15. The first functional layer contains a composition soluble in a fluorine-based solvent, Item 15. The automobile window glass according to any one of items 1 to 14, wherein the first functional layer has a thickness of 1 μm or less.
[0020] Item 16. An automobile window glass according to any one of Items 1 to 15, wherein the first functional layer has a dynamic friction coefficient of 0.15 or less.
[0021] Item 17. An automobile window glass according to any one of Items 1 to 16, further comprising a second functional layer laminated between the first functional layer and the surface of the glass body facing the vehicle interior, the second functional layer having at least one of an infrared ray blocking function, an ultraviolet ray blocking function, a low reflection function, a Low-e function, and an anti-fogging function.
[0022] Item 18. The automobile window glass according to any one of Items 1 to 17, wherein the first functional layer is further laminated on the vehicle exterior surface of the glass body.
[0023] Item 19. The automotive window glass according to item 18, wherein the region where the first functional layer is laminated on the vehicle inner surface of the glass body is different from the region where the first functional layer is laminated on the vehicle outer surface of the glass body.
[0024] Item 20. The automotive window glass according to item 18 or 19, further comprising a base layer laminated between the first functional layer on the vehicle exterior side and the glass surface on the vehicle exterior side.
[0025] Item 21. Dropping three drops of a test solution containing 10 μL of oleic acid onto the first functional layer; 1kg / 4cm 2 wiping the test liquid with a woven cloth at a load of 21. The automotive window glass according to any one of items 1 to 20, wherein the haze ratio measured after a test having the above properties is 1.0 or less.
[0026] Item 22. The automobile window glass according to item 21, wherein the number of wiping operations in the wiping step is 200 or less.
[0027] Item 23. The automobile window glass according to item 22, wherein the number of wiping operations in the wiping step is 150 or less.
[0028] In the inventions according to the above items 1 to 23, instead of the glass body, a plate-shaped resin material such as polyethylene (PE), polystyrene (PS), polyvinyl chloride (PVC), ABS, etc. may be used. Effect of the Invention
[0029] The automobile window glass according to the present invention can exhibit antifouling properties. [Brief description of the drawings]
[0030] [Figure 1] FIG. 4 is a plan view showing a second embodiment in which an automobile window glass according to the present invention is applied to a side glass. [Diagram 2] 2 is a cross-sectional view taken along line AA in FIG. 1. [Diagram 3] FIG. 3 is a schematic diagram illustrating bonding between a first functional layer and a glass plate. [Figure 4] FIG. 1 is a diagram illustrating a test for calculating a dynamic friction coefficient. [Diagram 5]It is a diagram for explaining the application of the coating liquid for the first functional layer by spraying. [Figure 6] It is a diagram showing the boundary of the first functional layer. [Figure 7] It is a plan view showing a second embodiment in which the window glass for automobiles according to the present invention is applied to a windshield. [Figure 8] It is a cross-sectional view taken along line B-B of FIG. 7. [Figure 9] It is a photograph showing the results in the comparative example of the test (evaluation 5) regarding scratches.
Mode for Carrying Out the Invention
[0031] <A. First Embodiment> First, with reference to FIGS. 1 and 2, an embodiment in which the window glass for automobiles according to the present embodiment is applied to a side glass will be described with reference to the drawings. FIG. 1 is a plan view of the side glass according to the present embodiment, and FIG. 2 is a cross-sectional view taken along line A-A of FIG. 1.
[0032] <1. Outline of Side Glass> As shown in FIGS. 1 and 2, this side glass includes a trapezoidal glass plate (glass body) 1 and a first functional layer 2 laminated on the inner surface 101 of the glass plate 1 on the vehicle interior side. Hereinafter, it will be described in detail.
[0033] <1-1. Glass Plate> The glass plate 1 is formed in a rectangular shape having an upper side 11, a lower side 12, a front side 13, and a rear side 14. The upper side 11 and the lower side 12 are formed in parallel, and the upper side 11 is shorter than the lower side 12. The front side 13 includes a first portion 131 that extends upward so as to incline rearward from the front end of the lower side 12, and a second portion 132 that extends further rearward so as to incline from the upper end of the first portion 131. Further, the rear side 14 extends upward so as to incline while being slightly curved rearward from the rear end of the lower side 12 substantially parallel to the first portion 131 of the front side 13. Therefore, the rear end of the upper side 11 is located slightly rearward of the rear end of the lower side 12.
[0034] The side glass made of the glass plate 1 is attached to the door of the vehicle, and is supported by a lifting module (regulator) (not shown) provided inside the door so that it can be raised and lowered. When the side glass is raised and the window is closed, the lower edge 12 of the side glass is located below the belt molding of the door. Therefore, the lower edge 12 of the side glass cannot be seen from the outside or inside of the vehicle regardless of whether the window is open or closed. At this time, the first functional layer 2 is not laminated in the area located below the belt molding. This area is referred to as the first non-laminated area (third area) 103. That is, the first functional layer 2 is laminated above the first non-laminated area 103, and the lower edge 104 of the first functional layer 2 is the boundary between the first functional layer 2 and the non-laminated area 103. A lifting module is attached to this first non-laminated area 103, or an adhesive or the like is applied thereto. In this way, the first functional layer 2 is provided with the first non-laminated region 103 in order to avoid a situation in which the first functional layer 2 contains fluorine and is unable to chemically bond with the adhesive, resulting in a decrease in adhesive performance. In addition to the first non-laminated region 103, the first functional layer 2 can also be left unlaminated in areas on the inside surface of the vehicle where stickers, such as anti-theft stickers, are affixed, forming a second non-laminated region (fourth region).
[0035] In addition, in the process of the side glass rising, the first portion 131 of the front side edge 13 and the rear side edge 14 are supported by a guide (for example, a glass run) of the door frame and move up and down along the guide. Therefore, the first portion 131 of the front side edge 13 and the rear side edge 14 are accommodated in the guide, and are therefore not visible from the outside and inside of the vehicle. When the window is closed, the second portion 132 of the front side edge 13 and the upper edge 11 are also accommodated in the door frame and are not visible from the outside and inside of the vehicle. It is also possible not to laminate the first functional layer 2 even in such an area accommodated in the door frame. However, the first functional layer 2 has a low dynamic friction coefficient as described later. In such a case, the first functional layer 2 may be laminated even in an area accommodated in the door frame. This is because the low dynamic friction coefficient makes it less likely to be scratched. In addition, when the thickness of the first functional layer 2 is small, the first functional layer 2 may be laminated even in an area accommodated in the door frame. This is because even if a scratch occurs, it is not noticeable. The test for scratches will be described later.
[0036] A known glass plate can be used as the glass plate 1, and it can be made of heat absorbing glass, general clear glass, green glass, or UV green glass. Examples of compositions of clear glass, heat absorbing glass, and soda lime glass are shown below.
[0037] (Clear glass) SiO2:70~73% by mass Al2O3:0.6~2.4% by mass CaO: 7~12% by mass MgO: 1.0~4.5% by mass RO: 13 to 15 mass% (R is an alkali metal) Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.08-0.14 mass%
[0038] (Heat absorbing glass) The composition of the heat ray absorbing glass can be, for example, based on the composition of clear glass, with the ratio of total iron oxide converted to Fe2O3 (T-Fe2O3) being 0.4 to 1.3 mass%, the ratio of CeO2 being 0 to 2 mass%, the ratio of TiO2 being 0 to 0.5 mass%, and the glass skeletal components (mainly SiO2 and Al2O3) being reduced by the increases in T-Fe2O3, CeO2, and TiO2.
[0039] (Soda-lime glass) SiO2: 65~80% by mass Al2O3: 0~5% by mass CaO: 5~15% by mass MgO: 2% by mass or more NaO: 10~18% by mass K2O: 0~5% by mass MgO+CaO: 5~15% by mass Na2O+K2O: 10~20% by mass SO3:0.05~0.3% by mass B2O3:0~5% by mass Total iron oxide converted to Fe2O3 (T-Fe2O3): 0.02-0.03 mass%
[0040] The thickness of the glass plate 1 is not particularly limited, but is preferably, for example, 2.4 to 5.2 mm, more preferably 2.6 to 3.4 mm, and particularly preferably 2.7 to 3.2 mm.
[0041] 2, the glass plate 1 is curved so as to be convex toward the exterior side of the vehicle, and a first functional layer 2 is laminated on a concave surface 101 facing the interior side of the vehicle. The radius of curvature of the concave surface 101 can be, for example, 15,000 to 50,000 mm, and is preferably 30,000 to 50,000 mm.
[0042] <1-2. 1st functional layer> Next, a description will be given of the first functional layer 2. The first functional layer 2 according to this embodiment contains a composition having antifouling properties.
[0043] The first functional layer 2 is characterized by containing substantially only a composition soluble in a fluorine-based solvent. Such a composition is not particularly limited, but may contain, for example, a compound represented by the following formula (X). Note that "substantially only a composition soluble in a fluorine-based solvent" does not mean, for example, to exclude other compositions that are mixed in during the manufacturing process, but means that the mixture of other compositions is allowed to be up to 1% by weight.
[0044] [Rf 1 -Z 1 ] a -Q 1 -[Z 2 -SiR c M 3-c ] b (X) (In the formula, Rf 1 are independently a monovalent perfluoropolyether group having a molecular weight of 400 to 20,000, which is composed of a perfluoroalkylene group having 1 to 6 carbon atoms and an oxygen atom, and Z 1 are each independently a divalent hydrocarbon group having 1 to 20 carbon atoms which may contain an oxygen atom, a nitrogen atom, or a silicon atom, and which may contain a cyclic structure in the middle. 2 are independently divalent hydrocarbon groups having 2 to 8 carbon atoms. 1 is a linking group having a valency of (a+b) containing at least (a+b) silicon atoms, and may form a cyclic structure. a is an integer of 1 to 10, b is independently an integer of 1 to 10, and c is independently 0, 1 or 2. a Z groups enclosed in [ ] in formula (X) 1 and b Z 2 are all Q 1 Or Q 2 It is bonded to the silicon atom in the structure. R is independently a monovalent hydrocarbon group of 1 to 6. M is an alkoxy group or an alkoxyalkyl group, -SiR c M 3-c is an alkoxysilyl group. The fluorine-containing reactive silane compound represented by the following formula (1) can be exemplified as a composition that is substantially soluble in a fluorine-based solvent.
[0045] Examples of the fluorine-containing reactive silane compound represented by the above formula (X) include those shown below. [ka] [ka] [ka] [ka] [ka] (In the formula, r1 and Rf' are the same as above.)
[0046] The number average molecular weight of the fluoropolyether chain portion in the perfluoroalkylene group is not particularly limited, but is, for example, 1,000 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. 19 The number average molecular weight is a value measured by F-NMR. When the number average molecular weight is 1000 or more, the molecular bonds become longer, and for example, as shown in FIG. 3, even if oil adheres to the first functional layer 2, the molecules are prevented from collapsing, and the deterioration of the antifouling performance can be prevented. On the other hand, if the number average molecular weight is too large, the number of alkoxysilyl groups bonded to the glass plate 1 may decrease. Therefore, when the number average molecular weight is 30,000 or less, the number of bonds with the OH groups of the glass plate 1 decreases, and the decrease in the bond strength can be prevented.
[0047] On the other hand, if the number average molecular weight of the fluoropolyether chain is less than 1,000, even if an alkoxysilyl group is contained, the reaction probability on the surface of the glass plate decreases. As a result, the abrasion resistance may decrease. In addition, if the molecular weight is low, as described later, the coating liquid for the first functional layer is easily vaporized, and especially when applying by spraying, it may be difficult to apply to a specified area.
[0048] The antifouling function of the first functional layer 2 means, for example, that it exhibits performance in a wiping test described below, and also means, for example, that the contact angle on the surface of the first functional layer is 60° or more, preferably 80° or more, and more preferably 100° or more.
[0049] The composition constituting the first functional layer 2 is dissolved in a fluorine-based solvent, and then laminated on the glass plate 1 by the method described below. Examples of the fluorine-based solvent include Perfluorohexane, Perfluorooctane, perfluoromethylcyclohexane, Perfluorodimethylcyclohexane, Perfluorodecalin, Perfluoroalkylethanol, Perfluorobenzene, Perfluorotoluene, Perfluoroalkylamines (Fluorinert (trade name), etc.), Perfluoroalkyl ethers, perfluorobutyltetrahydrofuran, Polyfluoroaliphatic hydrocarbons (Asahiclean AC6000 (product name)), Hydrochlorofluorocarbons (Asahiclean AK-225 (trade name) and the like), hydrofluoroethers (Novec (trade name), NOVEC7000 (trade name), NOVEC7100 (trade name), NOVEC7200 (trade name), NOVEC7300 (trade name), HFE-7100 (trade name), HFE-7200 (trade name), HFE-7300 (trade name), HFE-7000 (trade name), Asahiclean AE-3000 (trade name), and the like), 1,1,2,2,3,3,4-heptafluorocyclopentane, 1,1,1,3,3-pentafluorobutane, Fluorine-containing alcohol, Perfluoroalkyl bromides, Perfluoroalkyl iodides, perfluoropolyethers (Krytox (trade name), Demnum (product name), Fomblin (product name), etc. 1,3-bistrifluoromethylbenzene, 2-(perfluoroalkyl)ethyl methacrylate, 2-(perfluoroalkyl)ethyl acrylate, Perfluoroalkylethylene, Fluorocarbon 134a, and hexafluoropropene oligomers, 1,2-Dichloro-1,3,3,3-tetrafluoro-1-propene Some examples include:
[0050] The composition constituting the first functional layer 2 may be dissolved in a mixed solvent of a fluorine-based solvent and a second solvent, and then laminated on the glass plate 1 by a method described below. As the second solvent, a solvent that is miscible with the fluorine-based solvent and easily evaporates is preferable, for example, a low-viscosity silicone-based solvent. An example of a low-viscosity silicone-based solvent is silicone oil having a dimethylsiloxane structure and a kinetic viscosity of 3 mm at 25°C. 2 / s (3 centistokes) or less, and commercially available products include silicone oils such as KF-96L-0.65cs, KF-96L-1cs, KF-96L-1.5cs, and KF-96L-2cs manufactured by Shin-Etsu Chemical Co., Ltd.
[0051] <2. Properties and performance of the first functional layer> <2-1. Film thickness> The thickness of the first functional layer 2 is not particularly limited, but can be 1 μm or less. Specifically, for example, it is preferably 5 to 50 nm, and more preferably 10 to 30 nm. If the thickness of the first functional layer 2 exceeds 50 nm, the cost may be high. On the other hand, the first functional layer 2 exhibits an antifouling function even with a thin thickness such as a monolayer, but if it is less than 5 nm, for example, it may peel off from the glass plate 1 when an external force is applied before drying. Therefore, the thickness of the first functional layer 2 is preferably 5 nm or more. The thickness can be calculated by various methods, but for example, it can be measured by cutting the side glass at the place where the thickness is to be measured and observing the cross section with a SEM or the like.
[0052] Observation with the SEM can be performed, for example, as follows. A field emission scanning electron microscope S-4700 (manufactured by Hitachi High-Technologies Corporation) is used with an acceleration voltage of 5 kV. The first functional layer 2 is then etched with 0.1% hydrogen fluoride. After coating with Pt-Pd for conductive treatment, observation with the SEM is performed.
[0053] Furthermore, if the film thickness is large, for example, the above-mentioned alkoxysilyl groups may become excessive, and those that are not bonded to the glass plate 1 may appear on the surface of the first functional layer 2, forming unevenness. Such unevenness may prevent water droplets from flowing smoothly, and as a result, there is a risk of the antifouling performance being reduced.
[0054] <2-2. Water contact angle> The contact angle of water on the first functional layer 2 is preferably 60° or more, more preferably 80° or more, and particularly preferably 100° or more. A larger contact angle indicates better antifouling performance. It is known that the contact angle is generally 120° or less. The contact angle is measured, for example, with 3 μL of water using a contact angle measuring device ("DMs-401", Kyowa Interface Science Co., Ltd.).
[0055] <2-3. Friction coefficient> The dynamic friction coefficient of the first functional layer 2 is preferably 0.1 to 1.5, and more preferably 0.1 to 1.2. In particular, when the dynamic friction coefficient is 1.2 or less, the first functional layer 2 is slippery and therefore less likely to be scratched.
[0056] A test for calculating the dynamic friction coefficient can be performed, for example, as follows. First, as shown in FIG. 4, a glass plate 1 on which a first functional layer is laminated is placed on a flat base 80. The first functional layer is facing upward. The glass plate 1 is formed to a size of 100×50 mm. Then, a 0.686 N friction element (a dedicated friction element for TYPE-30S manufactured by Shinto Scientific Co., Ltd.) 81 is placed on the first functional layer. A #300 flannel cloth 83 is provided on the lower surface of this friction element 81, and the flannel cloth 83 is in contact with the first functional layer. Meanwhile, a 9.8 Nk weight 82 is placed on the upper surface of the friction element 81. Then, the friction element 81 is pulled in the horizontal direction at a speed of 500 mm / min by a tensile tester (Autograph AGS-10kNJ manufactured by Shimadzu Corporation) in an environment of room temperature (23° C.).
[0057] In this test, the load when the friction element 81 moves in the range from 10 mm to 70 mm was defined as Fk (N), and this was divided by the total load (9.8 N + 0.686 N) to calculate the dynamic friction coefficient.
[0058] <2-4. Wipe test> The abrasion test can be carried out, for example, as follows. First, three drops of a test liquid containing oleic acid, each drop being 10 μL, are dropped onto the first functional layer. Next, a dry flannel cloth (No. 300) is attached to a reciprocating abrasion tester ("HEIDON-18" manufactured by Shinto Scientific Co., Ltd.), and a pressure of 1 kg / 4 cm is applied to the surface of the first functional layer 2. 2 The test piece was then subjected to 400 reciprocating movements while applying a load of 1000 mm. After this test, the haze ratio was measured. The haze ratio can be measured, for example, using an integrating sphere type light transmittance measuring device (manufactured by Suga Test Instruments Co., Ltd., "HGM-2DP", using a C light source, with light incident from the first functional layer side). The haze ratio measured in this manner is preferably 1.0 or less. It is more preferable that the haze ratio after 200 reciprocating movements is 1.0 or less. After such an abrasion test, if the haze ratio is 1.0 or less, this means that the test liquid, i.e., the dirt, has been wiped off, and is an indicator of high antifouling properties.
[0059] <3. Manufacturing method of side glass> Next, a method for manufacturing the side glass will be described. First, a curved glass plate 1 is formed by known press molding or the like. Then, this glass plate 1 is transported by a conveyor or the like with the concave surface 101 facing upward. During this transport process, a pretreatment is performed on the concave surface 101 of the glass plate 1 before the first functional layer 2 is applied. The pretreatment is not particularly limited, but examples thereof include plasma treatment (corona discharge, etc.), ion beam treatment, alkali cleaning, and Cerico cleaning. Such treatment can introduce or increase hydroxyl groups on the surface of the concave surface 101 of the glass plate 1, and can also clean the concave surface 101 by removing foreign matter, etc.
[0060] After the Cerico cleaning, the surface of the glass plate 1 becomes hydrophilic, so the contact angle of the surface of the glass plate 1, i.e., the surface before the first functional layer 2 is laminated, is 100° or more. In addition, the surface roughness of the glass plate 1 is reduced after the Cerico cleaning. In particular, since the film thickness of the first functional layer 2 is thin, the surface roughness Ra of the first functional layer follows the surface roughness of the surface of the glass plate 1. As a result, the surface roughness Ra of the first functional layer can be set within the above-mentioned range, i.e., 3 nm or less.
[0061] Next, the coating liquid for the first functional layer 2 is applied to the concave surface 101 by spraying. The method of application using a spray device is not particularly limited, but for example, the glass plate 1 is transported by a conveyor as shown in Fig. 5. At this time, the glass plate 1 is transported in a direction perpendicular to the paper surface of Fig. 5.
[0062] The spray device is provided with two nozzles 5 arranged in parallel above the glass plate 1. From each nozzle, the coating liquid for the first functional layer 2 is sprayed toward the glass plate below at a coating angle θ of 100° or less. At this time, since the nozzles 5 are arranged close to each other, the coating liquid sprayed from the two nozzles 5 is applied so as to overlap. Since the coating liquid is sprayed from the nozzle 5 at a predetermined coating angle θ as described above, it is considered that the coating amount is the largest directly below the nozzle 5 on the concave surface of the glass plate 1, and the coating amount is small near the periphery. In addition, the coating amount is also large in the portion where the coating liquid sprayed from both nozzles 5 overlap. The height from the surface of the conveyor on which the glass plate 1 is placed to the nozzle 5 can be, for example, 20 to 80 mm. In addition, the amount of coating liquid discharged from each nozzle 5 can be, for example, 50 to 200 g / min.
[0063] In this example, the coating liquid is prevented from reaching the left end of the glass plate 1, and this portion becomes the above-mentioned non-laminated region 103. The coating liquid is sprayed from the nozzle 5 in a circular shape when viewed from above, and the glass plate 1 moves in the direction of the paper surface of Fig. 5, so that the boundary 104 between the non-laminated region 103 and the first functional layer 2 is formed in a wavy shape. However, it is also possible to prevent the first functional layer 2 from being coated by using masking.
[0064] For example, when a boundary 104 is formed as shown in FIG. 6, the maximum width d of the corrugated shape is preferably 1 to 20 mm.
[0065] In this embodiment, the coating liquid is sprayed from two nozzles 5, but one nozzle or three or more nozzles may be used.
[0066] After the coating liquid for the first functional layer is applied to the concave surface 101 in this manner, moisture may be subsequently supplied to the surface of the coating liquid. By supplying moisture, hydrolysis may be expected in some cases.
[0067] Next, the glass plate may be heated, for example, at a temperature of 100 to 200° C. In such an atmosphere, groups bonded to Si in the composition constituting the first functional layer rapidly undergo dehydration condensation, which may be expected to promote bonding between the composition and the concave surface 101.
[0068] Furthermore, since the fluorine-based solvent contained in the coating liquid evaporates quickly, the coating liquid flows toward the center along the concave surface 101 and hardens before pooling, thereby forming the first functional layer 2.
[0069] The method of applying the coating liquid for the first functional layer is not limited to the above, and for example, a flow coating method can be adopted. Also, the glass plate 1 can be supported at an angle and the coating liquid can be applied to it by spraying. By adopting such a method, the area to which the coating liquid is applied can be controlled.
[0070] <4. Features> According to the side glass described above, since the first functional layer has antifouling properties, adhesion of dirt can be prevented, or even if dirt does adhere, it can be easily removed. Note that dirt is caused by, for example, oily dirt such as fingerprints, or plasticizers generated from the decorative members inside the vehicle.
[0071] In addition, as the side glass rises and falls, static electricity is generated during the raising and lowering process. This can cause, for example, dust and dirt, as well as pieces of grease used in the lifting module, to adhere to the side glass. In contrast, the side glass of this embodiment has a low dynamic friction coefficient as described above, making it possible to suppress the generation of static electricity.
[0072] Furthermore, if the assembly precision of the lifting module is poor, the side glass may stop or turn over halfway when lifting or lowering. Such phenomena may also occur due to changes over time. In contrast, the side glass according to this embodiment has a low coefficient of dynamic friction, so the occurrence of such phenomena is suppressed.
[0073] <B. Second Embodiment> Next, a second embodiment in which the automotive window glass according to the present invention is applied to a windshield will be described with reference to the drawings. First, the configuration of the windshield according to this embodiment will be described with reference to FIGS. 7 and 8. FIG. 7 is a plan view of the windshield according to this embodiment, and FIG. 8 is a cross-sectional view taken along line B-B of FIG. 7. For the sake of convenience of explanation, the vertical direction in FIG. 7 will be referred to as "vertical", "perpendicular", "longitudinal", and the horizontal direction in FIG. 1 will be referred to as "horizontal".
[0074] As shown in FIG. 7, this windshield includes a horizontally long trapezoidal laminated glass (glass body) 10 and a shielding layer 4 laminated on the laminated glass 10. The laminated glass 10 has an outer glass plate 11, an inner glass plate 12, and an intermediate film 13 disposed between them. Further, as shown in FIG. 8, a first functional layer 2 is laminated on the inner surface of the inner glass plate 12 on the vehicle interior side, similarly to the first embodiment. Hereinafter, each component will be described in detail.
[0075] <1. Glass Plate> The same glass plates 11 and 12 as those shown in the first embodiment can be used. However, the thickness can be set as follows.
[0076] The thickness of this laminated glass 10 is not particularly limited, but the total thickness of the outer glass plate 11 and the inner glass plate 12 can be, for example, 2.1 to 6 mm. From the viewpoint of weight reduction, the total thickness of the outer glass plate 11 and the inner glass plate 12 is preferably 2.4 to 3.8 mm, more preferably 2.6 to 3.4 mm, and particularly preferably 2.7 to 3.2 mm.
[0077] The outer glass plate 11 is primarily required to have durability and impact resistance against external obstacles, and as a windshield for an automobile, it is required to have impact resistance against flying objects such as pebbles. On the other hand, the thicker the plate, the heavier it becomes, which is undesirable. From this viewpoint, the thickness of the outer glass plate 11 is preferably 0.7 to 5.0 mm, more preferably 1.5 to 3.0 mm, and particularly preferably 1.8 to 2.3 mm.
[0078] The thickness of the inner glass sheet 12 can be the same as that of the outer glass sheet 11, but can be made thicker or thinner than the outer glass sheet 11, for example, to reduce the weight of the laminated glass 10. Specifically, taking into account the strength of the glass, the thickness is preferably 0.3 to 3.0 mm, more preferably 0.7 to 2.3 mm, and particularly preferably 1.4 to 2.0 mm.
[0079] Furthermore, this laminated glass 10 is curved so as to be convex towards the outside of the vehicle, and in this case, the thickness is measured at two points above and below a center line extending vertically through the center in the left-right direction of the laminated glass 10. The measuring device is not particularly limited, but for example, a thickness gauge such as SM-112 manufactured by Techclock Corporation can be used. During measurement, the curved surface of the laminated glass 10 is placed on a flat surface, and the edge of the laminated glass 10 is clamped with the thickness gauge to perform the measurement.
[0080] <2. Interlayer film> The intermediate film 13 is formed of multiple layers, and as an example, as shown in FIG. 8, it can be configured of three layers in which a soft core layer 131 is sandwiched between harder outer layers 132. However, it is not limited to this configuration, and it may be formed of multiple layers having the soft core layer 131. For example, it can be formed of two layers including the core layer 131 (one core layer and one outer layer), or an odd number of layers of five or more layers arranged with the core layer 131 at the center (one core layer and four outer layers), or an even number of layers including the core layer 131 on the inside (one core layer and the other layers are outer layers). Alternatively, the intermediate film 13 can be configured of a single layer.
[0081] The core layer 131 can be formed of a material softer than the outer layer 132, but is not limited thereto. The materials constituting each layer 131, 132 are not particularly limited, but for example, the core layer can be formed of a material that makes it soft. For example, the outer layer 132 can be formed of polyvinyl butyral resin (PVB). Polyvinyl butyral resin is preferable because it has excellent adhesion to each glass plate and penetration resistance. On the other hand, the core layer 131 can be formed of ethylene vinyl acetate resin (EVA) or polyvinyl acetal resin that is softer than the polyvinyl butyral resin constituting the outer layer 132. By sandwiching the soft core layer 131, it is possible to greatly improve the sound insulation performance while maintaining the same adhesion and penetration resistance as a single-layer resin interlayer 3.
[0082] Furthermore, functional films having various functions can be used depending on the application as the core layer 131. For example, known heat shielding films, heat generating films, projection films, light emitting films, antenna films, etc. can be used.
[0083] The total thickness of the intermediate film 13 is not particularly limited, but is preferably 0.3 to 6.0 mm, more preferably 0.5 to 4.0 mm, and particularly preferably 0.6 to 2.0 mm. On the other hand, the thickness of the core layer 131 is preferably 0.1 to 2.0 mm, and more preferably 0.1 to 0.6 mm. If it is less than 0.1 mm, the soft core layer 131 is less likely to have an effect, and if it is more than 2.0 mm or 0.6 mm, the total thickness increases, resulting in increased costs. On the other hand, the thickness of the outer layer 132 is not particularly limited, but is preferably 0.1 to 2.0 mm, and more preferably 0.1 to 1.0 mm. Alternatively, the total thickness of the intermediate film 13 can be constant, and the thickness of the core layer 131 can be adjusted within this range.
[0084] The thickness of the interlayer film 13 does not need to be uniform over the entire surface, and may be wedge-shaped for use in laminated glass for head-up displays, for example. In this case, the thickness of the interlayer film 13 is measured at the thinnest point, that is, the bottom edge of the laminated glass.
[0085] The method for producing the intermediate film 13 is not particularly limited, and examples thereof include a method in which a resin component such as the above-mentioned polyvinyl acetal resin, a plasticizer, and other additives as necessary are blended and kneaded uniformly, and then each layer is extruded together, and a method in which two or more resin films produced by this method are laminated by a pressing method, a lamination method, etc. The resin films before lamination used in the lamination method by a pressing method, a lamination method, etc. may have a single layer structure or a multilayer structure.
[0086] <3. Shielding layer> As shown in FIG. 7, the shielding layer 4 is laminated on a dark color ceramic such as black on the inner glass plate of the laminated glass 10. The configuration of the shielding layer 4 is not particularly limited, but for example, as shown in FIG. 5, the shielding layer 4 includes a frame-shaped peripheral portion 41 arranged along the peripheral portion of the inner glass plate 12, and a rectangular extension portion 42 extending downward from the center of the peripheral portion 41 along the upper side of the inner glass plate 12. The extension portion 42 is formed with a shooting window 421 for a camera, so that the outside of the vehicle can be photographed by an on-board camera (not shown) provided on the inside of the vehicle. Alternatively, various sensors can be provided to receive light, signals, etc. from outside the vehicle through the shooting window 421. The extension portion 42 can also hide the bracket supporting the camera from being seen from outside the vehicle.
[0087] The shielding layer 4 may be laminated only on the surface of the inner glass sheet 12 facing the vehicle interior, or may be laminated only on the inner surface of the outer glass sheet 11, or on both the inner surfaces of the outer glass sheet 11 and the inner glass sheet 12, or in other various forms. The shielding layer 4 may be formed from ceramics and various other materials, and may have the following composition, for example.
[0088] [Table 1] *1, Main components: copper oxide, chromium oxide, iron oxide and manganese oxide *2, Main ingredients: bismuth borosilicate, zinc borosilicate
[0089] The ceramic can be formed by screen printing, but it can also be produced by transferring a firing transfer film to a glass plate and firing it. When using screen printing, for example, the following can be used: polyester screen: 355 mesh, coat thickness: 20 μm, tension: 20 Nm, squeegee hardness: 80 degrees, mounting angle: 75°, printing speed: 300 mm / s. The ceramic can be formed by drying in a drying oven at 150°C for 10 minutes.
[0090] The shielding layer 4 can be formed by laminating ceramics, or by attaching a dark-colored resin shielding film.
[0091] <4. 1st functional layer> The first functional layer 2 can be the same as in the first embodiment, so a detailed description will be omitted. The first functional layer 2 is not laminated over the entire surface of the inner side of the inner glass plate 12. That is, as shown in FIG. 8, the first functional layer 2 is not laminated near the outer edge of the peripheral portion 41 of the shielding layer 4, and the shielding layer 4 is exposed. This portion becomes the first non-laminated region (first region) 40. Furthermore, even in the region on the inner side of the inner glass plate 12 where the shielding layer 4 is not laminated, the first functional layer 2 is not laminated in some regions, forming a second non-laminated region (second region, not shown).
[0092] An adhesive is applied to the first non-laminated region 40, which allows the windshield to be attached to the vehicle body. Therefore, the first functional layer 2, which may hinder the application of the adhesive, is not laminated onto a part of the shielding layer 4. Also, the first functional layer 2 is not laminated onto the second non-contact region, since various sheets, such as vehicle inspection stickers, are affixed to the second non-contact region. Note that vehicle inspection stickers are often affixed outside the range of test region B defined by JIS R3212, and the second non-contact region may be provided outside such a region.
[0093] The method for laminating the first functional layer 2 is not particularly limited, but can be the same as that in the first embodiment, for example.
[0094] <5. Windshield manufacturing method> Next, an example of a method for manufacturing the windshield configured as above will be described. First, a method for manufacturing the laminated glass 10 will be described.
[0095] First, the above-mentioned shielding layer 4 is laminated on at least one of the flat outer glass plate 11 and the flat inner glass plate 12. Next, these glass plates 11, 12 are shaped so as to be curved. The shaping method is not particularly limited, and a known method can be adopted. For example, a flat glass plate passes through a heating furnace, and then is pressed by an upper mold and a lower mold to be shaped into a curved shape (pressing method). Alternatively, the flat glass plate is placed on a frame-shaped forming die and passed through a heating furnace. This causes the glass plate to soften, and the glass plate is shaped into a curved shape by its own weight (self-weight method).
[0096] Thus, when the outer glass plate 11 and the inner glass plate 12 are formed into a curved shape, subsequently, the intermediate film 13 is sandwiched between the outer glass plate 11 and the inner glass plate 12, placed in a rubber bag, and pre-bonded at about 70 to 110°C while performing vacuum suction. The method of pre-bonding can also be other than this. For example, the intermediate film 13 is sandwiched between the outer glass plate 11 and the inner glass plate 12 and heated at 45 to 65°C by an oven. Subsequently, this laminated glass is pressed by a roll at 0.45 to 0.55 MPa. Next, after heating this laminated glass again at 80 to 105°C by an oven, it is pressed again by a roll at 0.45 to 0.55 MPa. Thus, the pre-bonding is completed.
[0097] Next, the main bonding is performed. The laminated glass that has been pre-bonded is subjected to main bonding by an autoclave at, for example, 8 to 15 atmospheres and at 100 to 150°C. Specifically, for example, the main bonding can be performed under the conditions of 14 atmospheres and 145°C. Finally, as described above, the first functional layer 2 is laminated on the inner surface of the inner glass plate 12 on the vehicle interior side. Thus, the windshield according to the present embodiment is manufactured.
[0098] <6. Features> According to the windshield described above, since the first functional layer 2 has antifouling performance, similar to the first embodiment, it is possible to prevent dirt from adhering, or even if dirt adheres, it can be easily removed.
[0099] <C. Modification Example> As described above, one embodiment of the present invention has been described, but the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist thereof. Note that the following modification examples can be combined as appropriate.
[0100] <1> In the vehicle window glass of each of the above embodiments, the first functional layer is laminated only on the surface on the vehicle interior side, but the present invention is not limited to this, and a functional layer formed of the same material can also be laminated on the surface on the vehicle exterior side. In this case, for example, in the windshield of the second embodiment, as described above, the area on the vehicle interior side where the first functional layer 2 is laminated is specified, but on the vehicle exterior side, for example, the first functional layer 2 can be laminated on the entire surface. Therefore, in the windshield, the area on which the first functional layer 2 is laminated may differ between the surface on the vehicle interior side and the surface on the vehicle exterior side. On the other hand, when the first functional layer is laminated on the surface on the vehicle exterior side of the side glass, the area on which the first functional layer 2 is laminated can be the same on the surface on the vehicle interior side and the surface on the vehicle exterior side.
[0101] The first functional film having the above-mentioned composition also has water-repellent properties, and therefore when laminated on the surface facing the outside of a vehicle, it exhibits water-repellent properties against rain and the like.
[0102] <2> The side glass of the first embodiment is curved so that the inside of the vehicle is concave, but it can also be formed into a flat plate shape for vehicles such as buses. In the case of a flat plate shape, the first functional layer 2 may be applied to both sides. In this case, it is possible to avoid the mistake of installing it upside down when installing it in a vehicle such as a bus.
[0103] <3> In the vehicle window glass of each of the above-mentioned embodiments, a predetermined marking can be stamped. The predetermined marking is, for example, the name of the vehicle / glass manufacturer, a product number, a mark such as a JIS mark, a character, a figure, a symbol, etc., and is stamped on the surface of the glass sheet by a sandblasting method or the like. Such a marking may be formed on either the surface on the inside of the vehicle or the surface on the outside of the vehicle, or may be formed on both surfaces. Note that such a marking can be stamped before the glass sheet is cut into a predetermined shape.
[0104] <4> In the vehicle window glass of each of the above embodiments, another functional layer (second functional layer) can be laminated between the first functional layer 2 and the glass plate. Since the first functional layer 2 is a monomolecular film, there is a risk of moisture intrusion. Therefore, for example, by laminating a known infrared cut film, ultraviolet cut functional film, low reflection functional film, Low-e film, anti-fogging film, or other film, the intrusion of moisture can be prevented. In particular, by providing a water-absorbent anti-fogging film, the intruded moisture may be absorbed. In such a case, for example, the anti-fogging film can ensure the anti-fogging function. In addition, these films can also prevent the first functional layer 2 from being scratched. Furthermore, if there are unevenness on the surface such as fine particles or Low-e, there is a problem that fingerprint stains are difficult to remove, but by providing the first functional layer 2, there is an effect that fingerprint stains are difficult to attach.
[0105] <5> In the vehicle window glass of each of the above-mentioned embodiments, a base layer can be laminated between the first functional layer 2 laminated on the surface facing the vehicle exterior and the glass plate. This can suppress peeling of the first functional layer 2. The base layer can be a known one, and can be formed, for example, from evaporated silica.
[0106] <6> The shape of the glass plate is not particularly limited, and can be various shapes. In addition, in each of the above embodiments, the automotive window glass according to the present invention is applied to a side glass or a windshield that can be raised and lowered, but the present invention is not limited thereto, and can also be applied to a fixed side glass or a rear glass that cannot be raised and lowered. In addition, for example, applying the first functional layer 2 to an automotive window glass provided with a defogger or an antenna conductor is also suitable as a measure against discoloration and disconnection.
[0107] <7> The application method for the first functional layer 2 is not limited to the above-mentioned method, and for example, the layer may be applied by hand by an operator. EXAMPLES
[0108] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0109] First, the glass plate and the first functional layer used in the examples and comparative examples were prepared as follows.
[0110] (1) Glass plate A rectangular float glass plate having a size of 1000×500 mm and a thickness of 3 mm was prepared. This glass plate was curved, and the radius of curvature of the concave surface was 650 mm.
[0111] (2) 1st functional layer As the first functional layer to be applied to the concave surface of the glass plate according to Example 1, a water repellent agent was prepared by dissolving KY-1901 manufactured by Shin-Etsu Chemical Co., Ltd. in a fluorine-based solvent, and the water repellent agent was applied to the glass plate by spraying, and then dried in the same manner as in the first embodiment. This water repellent agent contains an alkoxysilyl group as a coupling agent, and has an average molecular weight of 1,000 or more.
[0112] As the first functional layer to be applied to the concave surface of the glass plate according to Example 2, a water repellent agent was prepared by dissolving Optool UD120 manufactured by Daikin Industries, Ltd. in a mixed solvent of fluorine-based solvent NOVEC7300 and silicone-based solvent KF-96L-1cs in a mass ratio of 7:3, and the water repellent agent was applied to the glass plate by spraying, and then dried in the same manner as in the first embodiment. This water repellent agent contains an alkoxysilyl group as a coupling agent, and has an average molecular weight of 1,000 or more.
[0113] As the first functional layer to be applied to the concave surface of the glass plate according to Example 3, a water repellent agent was prepared by dissolving Optool UD120 manufactured by Daikin Industries, Ltd. in a fluorine-based solvent AC6000.
[0114] As the first functional layer to be applied to the concave surface of the glass plate in Example 4, a water repellent agent was prepared by dissolving Optool UD120 manufactured by Daikin Industries, Ltd. in a mixed solvent of fluorine-based solvent AC6000 and silicone-based solvent KF-96L-1cs in a mass ratio of 7:3, and the water repellent was applied to the glass plate by spraying.Then, the coating was dried in the same manner as in Example 1, as shown in the first embodiment above.
[0115] On the other hand, the glass plate according to the comparative example does not have the first functional layer laminated thereon.
[0116] (3) Rating 1 The above-mentioned wiping test was carried out on Examples 1 to 4 and the Comparative Example, and the haze ratio was measured. The results are as follows. [Table 2] [Table 3]
[0117] (4) Rating 2 A plasticizer (DOP: a plasticizer for plastisol) was applied to the glass plate in accordance with ISO 6452. After that, the glass plate was wiped off in the same manner as in the above-mentioned wiping test, and the haze ratio was measured. The results are as follows. [Table 4]
[0118] (5) Rating 3 An appropriate amount of oleic acid was extruded from a syringe onto a glass plate to adhere to the surface of the glass plate. Then, the contact angle of oleic acid was measured for the three examples 1 to 4 and the comparative example. The results are as follows. [Table 5]
[0119] (6) Rating 4 The dynamic friction coefficients were calculated as described above for the three Examples 1 to 4 and the Comparative Example, and the results are as follows. [Table 6]
[0120] (7) Rating 5 A 10×10 mm steel wool was pressed against Examples 1 to 4 and the Comparative Example with a load of 1 kg, and moved over a distance of 50 mm at a speed of 120 mm / s. After 3000 movements, the surfaces were observed and no noticeable scratches were found in Examples 1 to 4. On the other hand, scratches were found in the Comparative Example, as shown by the arrows in FIG. 9.
[0121] (8) Discussion Regarding evaluation 1, in Examples 1 to 4, the haze ratio was 0.6 after 200 wipes. Therefore, it was found that dirt was easy to wipe off. On the other hand, in the comparative example, the haze ratio was 11 even after 400 wipes, and it was found that dirt was difficult to wipe off. Therefore, it was found that the first functional layer exhibited antifouling performance. This point was also the same in evaluation 2, and it was found that the present invention was also effective in wiping off the attached plasticizer.
[0122] Regarding evaluation 3, it was found that when oleic acid adheres to a glass plate, the contact angle decreases, but when the first functional layer is laminated as in Examples 1 to 4, the contact angle does not decrease.
[0123] As shown in evaluation 4, it was found that the provision of the first functional layer reduced the dynamic friction coefficient. Furthermore, as shown in evaluation 5, it was also found that the provision of the first functional layer made it less susceptible to scratches. [Explanation of symbols]
[0124] 1 Glass plate 2 1st functional layer
Claims
1. An automobile window glass comprising: A plate-shaped glass body; A first functional layer is laminated on the surface of the glass body facing the vehicle interior and has at least an antifouling property; Equipped with Dropping three drops of a test solution, each drop containing 10 μL of oleic acid, onto the first functional layer; wiping off the test liquid with a woven cloth under a load of 1 kg / 4 cm2; The haze ratio measured after a wipe test having a thickness of 1.0 or less is an automotive window glass.
2. 2. The automobile window glass according to claim 1, wherein a predetermined marking is stamped on an inner surface of the glass body facing the vehicle.
3. 2. The automobile window glass according to claim 1, wherein a predetermined marking is stamped on the surface of the glass body facing the vehicle exterior.
4. 4. The window glass for an automobile according to claim 1, wherein the glass body is curved so that the interior side of the automobile is concave.
5. The automobile window glass according to claim 1 , wherein the glass body is formed into a flat plate shape.
6. Further, a shielding layer is laminated on a part of the surface of the glass body on the vehicle interior side, 6. The automotive window glass according to claim 1, wherein the first functional layer is laminated on at least a portion of the region where the shielding layer is not laminated on the vehicle interior surface of the glass body and on at least a portion of the shielding layer.
7. The automotive window glass according to claim 6 , wherein the shielding layer has a first region where the first functional layer is not laminated.
8. 8. The automotive window glass according to claim 7, wherein the first region is a contact portion with a vehicle body.
9. 8. An automotive glazing as claimed in claim 7, wherein the first area is an area for mounting a component.
10. The glass body is a windshield, 10. The automotive window glass according to claim 6, wherein a second region in which the first functional layer is not laminated is provided in an area on the vehicle interior side of the glass body where the shielding layer is not laminated.
11. The glass body is a side glass, A third region in which the first functional layer is not laminated is provided along the lower edge of the glass body, 5. The automotive window glass according to claim 1, wherein a part supporting the side glass is attached to the third region.
12. The glass body is a side glass, 5. The automotive window glass according to claim 1, further comprising a fourth region on an interior side of the glass body, the fourth region being free of the first functional layer.
13. The automotive window glass according to claim 11, wherein the boundary between the first functional layer and the third region is formed in a wavy shape.
14. 14. The automotive window glass according to claim 1, wherein the average molecular weight of the composition exhibiting the antifouling property in the first functional layer is 1,000 or more and 30,000 or less.
15. The first functional layer contains a composition soluble in a fluorine-based solvent, 15. An automotive window glass according to claim 1, wherein the first functional layer has a thickness of 1 μm or less.
16. 16. An automotive window glass according to claim 1, wherein the first functional layer has a dynamic friction coefficient of 0.15 or less.
17. 17. The automotive window glass according to claim 1, further comprising a second functional layer laminated between the first functional layer and the surface of the glass body facing the vehicle interior, the second functional layer having at least one of an infrared ray blocking function, an ultraviolet ray blocking function, a low reflection function, a Low-e function, and an anti-fogging function.
18. The automotive window glass according to claim 1 , further comprising the first functional layer laminated on an exterior surface of the glass body.
19. 19. The automotive window glass according to claim 18, wherein an area where the first functional layer is laminated on the vehicle inner surface of the glass body is different from an area where the first functional layer is laminated on the vehicle outer surface of the glass body.
20. 20. The automotive window glass according to claim 18, further comprising a base layer laminated between the first functional layer on the vehicle exterior side and the glass surface on the vehicle exterior side.
21. 21. The automotive window glass according to claim 1, wherein the number of wiping operations in the wiping step is 200 or less.
22. 22. The automotive window glass of claim 21, wherein the wiping step comprises 150 or fewer wipes.
Citation Information
Patent Citations
Area setting ruler
JP2005114659A
Area indicator
JP2005145339A
Window glass with coating for vehicle
JP2016020204A
Window glass and application method of liquid for functional membrane
JP2016055828A
Glass plate and manufacturing method of glass plate
JP2016101826A